Bhoṭāntika jana-jāti : aitihāsika-sāṃskrtika evaṃ samājaśastrīya adhyayana - Jośī, Avanīndra Kumāra (Prakāśa Buka Ḍipo, 1983)
Sociocultural study of Bhotias, Tibetan people living in the Garhwal region, Uttar Pradesh.